Atomic-scale insight into non-crystallographic slip traces in body-centred cubic crystals. (15th March 2019) - Douat, Benjamin; Coupeau, Christophe; Bonneville, Joël; Drouet, Michel; Vernisse, Loranne; Kubin, Ladislas
Abstract: At low and moderate temperatures, dislocation motion propagates plastic flow in crystals through the shearing of dense crystallographic planes by an elementary translation. Almost one century ago, it was discovered that body-centred cubic metals behave differently and slip may occur in 'non-crystallographic' planes. Till now slip trace examinations were performed using current imaging and diffraction techniques. A homemade deformation device coupled to a scanning tunneling microscope made it possible to examine (as here shown in niobium crystals) slip traces with atomic resolution. The traces consist of several atomic step combinations, of which the related crystallographic planes were identified. Graphical Abstract: